2006
DOI: 10.1056/nejmoa052825
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Donor C3 Allotype on Late Renal-Transplantation Outcome

Abstract: Expression of C3 alleles by donor renal cells appears to have a differential effect on late graft outcome. Among white C3S/S recipients, receipt of a C3F/F or C3F/S donor kidney, rather than a C3S/S donor kidney, is associated with a significantly better long-term outcome. These findings suggest that the two alleles have functional differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 32 publications
2
108
0
4
Order By: Relevance
“…The same variant appears to affect the outcome of renal transplantation. 74 A 1972 study of the fast and slow variants found no difference in haemolytic activity. 75 There have been no recent published functional studies of the effect of this polymorphism and so the mechanism of its effect in AMD is not yet known.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 96%
“…The same variant appears to affect the outcome of renal transplantation. 74 A 1972 study of the fast and slow variants found no difference in haemolytic activity. 75 There have been no recent published functional studies of the effect of this polymorphism and so the mechanism of its effect in AMD is not yet known.…”
Section: Genetic Variants Of Complement Genes Associated With Amd Andmentioning
confidence: 96%
“…Complement is important at many stages during the course of a kidney transplant: complement polymorphisms may alter outcome after transplantation [63] , complement gene expression is increased in preimplantation biopsies and this can predict outcome [64] , complement has a role in the development of ischaemia reperfusion injury [65] and augments the alloimmune response [66] . All of these factors may impact upon longterm transplant outcome, however it is the role of complement in antibody mediated rejection (AMR) that has generated most interest recently.…”
Section: Complement and Progressive Loss Of Transplant Functionmentioning
confidence: 99%
“…Carries of C3F allele are at risk for the development of age-related macular degeneration (AMD) [46], partial lipodystrophy (PD) [51], and various types of GN: membranoproliferative glomerulonephritis type II (MPGN II, presently known as dense deposit disease, DDD) [51,52], IgA nephropathy (IgAN) [53,54] and systemic vasculitis (SV) [55,56]. Surprisingly, C3F allele has been shown to have a protective effect on transplant kidney, and its presence in donor's kidney may prolong the graft survival [57]. The common C3S/F comprises approximately 98% of all C3 phenotypes.…”
Section: The Genetic Background Of the Ap Abnormalities In Glomerularmentioning
confidence: 99%